If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2sin(2x) Remove parenthesis around (2x) 0 = 2ins * 2x Reorder the terms for easier multiplication: 0 = 2 * 2ins * x Multiply 2 * 2 0 = 4ins * x Multiply ins * x 0 = 4insx Solving 0 = 4insx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-4insx' to each side of the equation. 0 + -4insx = 4insx + -4insx Remove the zero: -4insx = 4insx + -4insx Combine like terms: 4insx + -4insx = 0 -4insx = 0 Divide each side by '-4'. insx = 0 Simplifying insx = 0 The solution to this equation could not be determined.
| 8v+w+7-8w+2w= | | m+3.5=4.2 | | 2(3h-7)=76 | | 3x+(-3x)=5 | | 2+3x+4-1= | | 0.16y+0.08(y+9000)=2400 | | 6(t-3)+4t=5(2t+5)-13 | | .11x-400-.03x=840 | | 4x+6+3x+4=(-40)+4 | | 3z-836=-77 | | Y+8=2y-4 | | -3x+10=94+4x | | 5y^2-7y=-2 | | 27=3(2x-7) | | -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 | | (2x-4)-(5x+3)= | | 4c-43=7c-193 |